Dental health education for students of SDN 09 Air Pacah Kota Padang through audiovisual kinesthetic media in the form of singing and simulation of how to brush teeth: Dental health education pada siswa SDN 09 Air Pacah Kota Padang melalui media audiovisual kinestetik berupa menyanyi dan simulasi cara menyikat gigi - Aisyah, Siti; Sativa, Puti; Ayu, Suci Lia; Fhadhila, Tiara; Surya, Leny Sang; Zia, Hanim Khalida; Pertiwi, Oniel Syukma; Pujiyati, Alfiyah; Andriansyah (Makassar Dental Journal PDGI Makassar, 2025)
Oral health knowledge should be given to school-age children. Elementary school is a very strategic group for oral health mana-gement. Audiovisual kinesthetic media is included in multimedia which contains three elements, namely visual elements (ima-ges), audio elements (sound) and motion elements at the same time. The purpose of this counseling is to change children's beha-viour in maintaining oral health. This activity was carried out in August 2024 with 35 students attending. This counselling activity for children at SDN 09 Air Pacah has gone well. The method of counselling by means of practice or demonstration was able to improve children's understanding, especially in practicing how to brush their teeth properly; even counselling by singing songs also had an effect on changes in knowledge, attitudes and application of toothbrushing actions in school-age children.